(untitled) (Bangladesh Journal of Medical Science, 2013)
Nerve sheath tumors of gastrointestinal tract are rare and occurs more frequently as systemic manifestations of generalized neurofibromatosis type-1(NF-1). In neurofibromatosis-1 lesions may be scattered or solitary tumor. Occasionally, such tumors may be the initial presenting feature of NF-1. Rarely, cases of isolated nerve sheath tumor of small intestine presenting with bleeding and obstruction have been documented. We report a 19years male presenting with nerve sheath tumor of jejunum in acute abdomen. His investigations show no features of NF-1. DOI: http://dx.doi.org/10.3329/bjms.v12i1.11754 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.91-92